An integrated A/C and HDH water desalination system assisted by solar energy: Transient analysis and economical study. (5th September 2016) - Fouda, A.; Nada, S.A.; Elattar, H.F.
Highlights: Hybrid A/C and HDH desalination system solar assisted are proposed. Transient analysis and parametrical study for system performance are presented. Effects of operating and design parameters on the proposed system is investigated. System capacity, consumption, performance and cost saving analysis are hourly and daily investigated and presented. Proposed system operates more efficient in more hot and humid climatic conditions. Abstract: Theoretical investigation on the performance of a proposed innovated solar integrated system for air conditioning (A/C) and humidification dehumidification (HDH) water desalination in hot and humid regions is presented. Transient analysis and parametrical study for the system are conducted under different operating and design conditions. System performance parameters (fresh water production rate, cooling capacity, electrical power consumption, water recovery and system coefficient of performance) are hourly estimated and daily integrated for different operational and design conditions. The results reveal the increase of fresh water productivity, system water recovery, cooling capacity, electrical power consumption and COP of the system with the increase of air temperature, air humidity, and solar collectors area. For system assessment, the system performance parameters are compared with the performance of a basic system under the same conditions. Cost saving analysis showed the proposed system operates more economically and efficiently that in hot and humid climatic areas. General numerical correlations for system performance parameters are proposed in terms of the design and operational conditions.